2010
DOI: 10.1136/qshc.2008.030213
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and associated enablers of, and barriers to, adverse incident reporting

Abstract: Enablers to incident reporting have been shown to be associated not only with reporting per se but also with changes to reporting patterns and rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 24 publications
3
66
0
1
Order By: Relevance
“…Incident reporting is one of the key mechanisms to achieve this learning, but in practice many organisations are struggling to extract the kind of information that allows lessons that are of immediate relevance to the local work environment to be learned effectively. The interviews conducted as part of this study confirmed some of the barriers to successful incident reporting that had been identified in the literature previously [21][22][23][24][25], such as lack of feedback about what happens with incident reports once they are submitted, the absence of improvements to the local work environment as a result of incident reports and uncertainty about the incident reporting process in general. The PRIMO approach to organisational learning -intended to operate alongside local incident reporting -aims to overcome these barriers by emphasising participation and ownership of staff, and by producing visible improvements to the local work environment.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Incident reporting is one of the key mechanisms to achieve this learning, but in practice many organisations are struggling to extract the kind of information that allows lessons that are of immediate relevance to the local work environment to be learned effectively. The interviews conducted as part of this study confirmed some of the barriers to successful incident reporting that had been identified in the literature previously [21][22][23][24][25], such as lack of feedback about what happens with incident reports once they are submitted, the absence of improvements to the local work environment as a result of incident reports and uncertainty about the incident reporting process in general. The PRIMO approach to organisational learning -intended to operate alongside local incident reporting -aims to overcome these barriers by emphasising participation and ownership of staff, and by producing visible improvements to the local work environment.…”
Section: Resultsmentioning
confidence: 56%
“…Appeared in: Reliability Engineering & System Safety 2012;101: [21][22][23][24][25][26][27][28][29][30][31][32][33][34] The author is grateful to the site members of the Safer Clinical Systems project who implemented the approach locally and to all participating staff of the hospital pharmacy. The work was commissioned by the Health Foundation, London (Registered Charity Number: 286967).…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such barriers include, for example, fear of blame and repercussions, poor usability of incident reporting systems, perceptions among doctors that incident reporting is a nursing process, lack of feedback to staff who report incidents, and lack of visible improvements to the local work environment as a result of reported incidents [67,68,[70][71][72][73]. Among management staff in particular, there continues to be widespread misperception that incident reporting systems might be useful for monitoring incident frequencies, despite evidence that suggests that incident reporting data are poor indicators of actual incident frequencies [74].…”
Section: The Challenges Of Organisational Learning In Healthcarementioning
confidence: 99%
“…There are a staggering number of incidents reported every year. However, despite the large number of potential learning opportunities, questions have been raised about the effectiveness of incident reporting systems to contribute to improvements in patient safety [19,[66][67][68][69]. There are now many studies that document barriers to effective incident reporting in health care.…”
Section: The Challenges Of Organisational Learning In Healthcarementioning
confidence: 99%